2014
DOI: 10.1080/08897077.2014.954026
|View full text |Cite
|
Sign up to set email alerts
|

Baylor Pediatric SBIRT Medical Residency Training Program: Model Description and Evaluation

Abstract: SBIRT skills training can be incorporated into pediatric residency training, and residents are able to learn and implement the skills in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…42,46-48,50-57,59,60,63,69,72-75,77,79,82-88,90-94,96-98,101,104-109,111,112,114-120,123,124,126-,127,130-132 Additionally, 23 (28%) used objective measures of SBIRT/MI skill outcomes, 42,[49][50][51]54,61,65,68,70,71,[76][77][78]80,84,90,92,100,104,105,109,110,[114][115][116][117]126,132,133 6 of which used measures with published psychometrics. 42,51,71,104,105,[114][115][116] In terms of trainee implementation of SBIRT, 26 (31%) studies measured some form of implementation posttraining. [43][44][45][46][47][48]51,59,60,[62][63][64]73,…”
Section: Coaching and Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…42,46-48,50-57,59,60,63,69,72-75,77,79,82-88,90-94,96-98,101,104-109,111,112,114-120,123,124,126-,127,130-132 Additionally, 23 (28%) used objective measures of SBIRT/MI skill outcomes, 42,[49][50][51]54,61,65,68,70,71,[76][77][78]80,84,90,92,100,104,105,109,110,[114][115][116][117]126,132,133 6 of which used measures with published psychometrics. 42,51,71,104,105,[114][115][116] In terms of trainee implementation of SBIRT, 26 (31%) studies measured some form of implementation posttraining. [43][44][45][46][47][48]51,59,60,[62][63][64]73,…”
Section: Coaching and Feedbackmentioning
confidence: 99%
“…Of the studies reporting SBIRT or MI training methods (Table 2), 26 (33%) studies indicated that faculty trainers delivered some sort of coaching or feedback to trainees regarding their SBIRT performance 47,50,51,[59][60][61]68,69,71,77,78,80,82,86,88-90,94, 95,99,100, [107][108][109][110]114,115,117,126,128,[131][132][133][134]136 and 13 (24%) gave feedback on MI performance. 50,[59][60][61]77,78,86,88,90,95,[107][108][109]126,131,134,136 A similar number of studies used an objective measure to provide coaching or feedback on SBIRT (n = 22, 28%) 42,49,51,54,[59][60][61]68,70,75,78,80,82,84,…”
Section: Coaching and Feedbackmentioning
confidence: 99%
“…First, more supervisors need to be trained so that they can serve as SBIRT champions who encourage students' implementation of this intervention and so they can provide supervision of and feedback to students. Ongoing discussion of SBIRT skills, coaching, and supervision are necessary for mastery of SBIRT and for sustaining use of SBIRT with clients (Bray et al, 2014;Miller, Sorensen, Selzer, & Brigham, 2006;Ogden et al, 2016). From the data we gathered from field supervisors on their training preferences, it appears that most supervisors thought future SBIRT trainings would be helpful: About 25% preferred that future trainings be held outside of their organization, and a similar percentage preferred that the training be offered within their organization.…”
Section: Facilitators Of and Barriers To Implementing And Sustaining ...mentioning
confidence: 99%
“…In all of the studies we have reviewed, regardless of the modality or training approach, the overwhelming majority of training participants reported they were satisfied with the training experience and found it helpful to their careers. In general, face-to-face and online training programs have both demonstrated efficacy in increasing SBIRT knowledge, self-efficacy, and use of SBIRT skills in clinical practice (Bray et al, 2014;Sacco et al, 2017;Stoner et al, 2014;Tanner et al, 2012) and increasing the use of SBIRT in practice (e.g., Bray et al, 2014;Tetrault et al, 2012). In a study of baccalaureate nursing students, Knopf-Amelung et al (2018) evaluated three didactic instruction methods for teaching students about SBIRT: (a) in-person, (b) asynchronous narrated slides, and (c) interactive online instruction.…”
Section: Training Modalitiesmentioning
confidence: 99%
“…To address this lack of training, the Substance Abuse and Mental Health Services Administration (SAMHSA) provides SBIRT resources to adopt into training curricula. To date, training for SBIRT has been implemented in several residency programs nationally, mostly in primary care specialties but also within some EM programs 6,7. While some work has been conducted with medical students, residents and faculty, training for other future ED providers, ie, physician assistant (PA) students, has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%